1993
DOI: 10.1111/j.1525-1446.1993.tb00032.x
|View full text |Cite
|
Sign up to set email alerts
|

Health, Income, and Postretirement Employment of Older Adults

Abstract: After a poor response to advertisements for employment for older adults, a community health nursing agency surveyed 216 individuals ranging in age from 60 to 96 years to examine their attitudes toward postretirement work, perceptions of barriers to and facilitators of employment, and the influence of perceived health status and income on these factors related to labor force participation. The findings are consistent with continuity theory of aging, and underscore the need for public policies aimed at supportin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1998
1998
2021
2021

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…To examine how financial needs influence work after retirement, numerous studies have used income as a proxy for financial need. Most studies have found that individuals with greater wealth (Burkert & Hockfellner, 2017;de Wind, van der Pas, Blatter, & van der Beek, 2016;Dingemans, Henkens, & van Solinge, 2015;Fontana & Frey, 1990;Pattersson, 2014;Toughill, Mason, Beck, & Christopher, 1993;Yang, 2011), including total household income (Gonzales, Lee, & Brown, 2017) and pension income (Burtless & Moffitt, 1985;Cho, Lee, & Woo, 2016;Deller, Liedtke, & Maxin, 2009;Gonzales et al, 2017;Holden, 1988;Moen & Flood, 2013;Pleau, 2010;Rad, Rashidian, Arab, & Souri, 2017;Ruhm, 1990;Saba & Guerin, 2005), were less likely to engage in postretirement employment. Some scholars, however, have called the simple linear relationship between financial need and work after retirement into question, arguing that the relationship is more complex.…”
Section: Needsmentioning
confidence: 99%
See 1 more Smart Citation
“…To examine how financial needs influence work after retirement, numerous studies have used income as a proxy for financial need. Most studies have found that individuals with greater wealth (Burkert & Hockfellner, 2017;de Wind, van der Pas, Blatter, & van der Beek, 2016;Dingemans, Henkens, & van Solinge, 2015;Fontana & Frey, 1990;Pattersson, 2014;Toughill, Mason, Beck, & Christopher, 1993;Yang, 2011), including total household income (Gonzales, Lee, & Brown, 2017) and pension income (Burtless & Moffitt, 1985;Cho, Lee, & Woo, 2016;Deller, Liedtke, & Maxin, 2009;Gonzales et al, 2017;Holden, 1988;Moen & Flood, 2013;Pleau, 2010;Rad, Rashidian, Arab, & Souri, 2017;Ruhm, 1990;Saba & Guerin, 2005), were less likely to engage in postretirement employment. Some scholars, however, have called the simple linear relationship between financial need and work after retirement into question, arguing that the relationship is more complex.…”
Section: Needsmentioning
confidence: 99%
“…Health. Not surprisingly, many studies have found a positive relationship between good physical health and the likelihood of working after retirement (Cahill, Giandrea, & Quinn, 2011;de Wind et al, 2016;Dingemans et al, 2015;Gonzales et al, 2017;Griffin & Hesketh, 2008;Hayward et al, 1994;Holden, 1988;Kim & Feldman, 2000;Pleau, 2010;Ruhm, 1994;Saba & Guerin, 2005;Toughill et al, 1993;van Solinge, 2014;Wang et al, 2008). However, given increasing concerns about dementia as a greater portion of the world's population is now ages 60 and over (United Nations, 2017), it was somewhat surprising that few studies have examined the relationship between mental health and postretirement work engagement.…”
Section: Demographics As Signals Of Human Capitalmentioning
confidence: 99%
“…Thirdly, there is a body of literature highlighting the role of social security benefits in incentivising early retirement, particularly among men (Gruber and Wise, 1998; Marmora, 2015), and more broadly their impact on the employment outcomes of those on low incomes or housing assistance (Beer et al, 2016; Feeny et al, 2012). Unsurprisingly, the literature confirms health conditions as a key driver of older persons’ labour force exits (Toughill et al, 1993; Roy, 2018).…”
Section: Literature Reviewmentioning
confidence: 99%